# If α and β are the roots of x2- 2x +4 = 0, then the value of α6 + β6 is

1.  32

2.  64

3.  128

4.  256

4

128

Explanation :
No Explanation available for this question

# The locus of z satisfying the inequalitywhere z = x + iy, is

1.  x2 + y2 < 1

2.  x2 - y2 < 1

3.  x2 + y2 > 1

4.  2x2 + 3y2 < 1

4

x<sup>2</sup> + y<sup>2</sup> &gt; 1<br>

Explanation :
No Explanation available for this question

# If n is an integer which leaves remainder one when divided by three, then  (1 + √3i )n + (1 - √3i )n  =

1.  -2n+1

2.  2n+1

3.  -(-2)n

4.  -2n

4

-(-2)<sup>n</sup>

Explanation :
No Explanation available for this question

# The period of sin4 x + cos4 x is

1.  π4  / 2

2.  π2  / 2

3.  π  / 4

4.  π  / 2

4

&#960;&nbsp; / 2<br>

Explanation :
No Explanation available for this question

1.  (1 + λ ) /  (1 - λ)

2.  (1 - λ ) /  (1 + λ)

3.   λ  /  (1 +λ)

4.   λ) /  (1 - λ)

4

(1 - &#955; ) /&nbsp; (1 + &#955;)<br>

Explanation :
No Explanation available for this question

# cos A cos 2A cos 4A.......................cos 2n-1 A =

1.  sin 2n A  / 2n sin A

2.  2n sin 2n A  /  sin A

3.  2n sin A /   sin 2n A

4.  sin A / 2n sin 2n A

4

sin 2<sup>n</sup> A&nbsp; / 2<sup>n</sup> sin A

Explanation :
No Explanation available for this question

# If 3 cos x ≠ 2 sin x then the general solution of sin2 x - cos 2x = 2 - sin 2x is x =

1.  nπ + (-1)n  π/2   , n Є  Z

2.  nπ/2  , n   Є   Z

3.  (4n+1)π/2 , n  Є  Z

4.  (2n-1)π  , n  Є  Z

4

(4n+1)&#960;/2 , n&nbsp; &#1028;&nbsp; Z

Explanation :
No Explanation available for this question

# cos-1(-1/2) - 2sin-1(1/2) + 3cos-1(-1/√2) - 4tan-1(-1) =

1.  19π / 12

2.  35π/12

3.  47π/12

4.  43π/12

4

43&#960;/12

Explanation :
No Explanation available for this question

# sinh-1 2 +sinh-1 3 = x ==> cosh x =

1.  1/2  ( 3√5 + 2√10)

2.  1/2  ( 3√5 - 2√10)

3.  1/2  ( 12 + 2√50)

4.  1/2  ( 12 -2√50)

4

1/2&nbsp; ( 12 + 2&#8730;50)<br>

Explanation :
No Explanation available for this question

# In any ∆ ABC, a(b cos C - c cos B) =

1.  b2 + c2

2.  b2 - c2

3.  1/b  +  1/c

4.  1/b2   +  1/ c2

4